Handbook of blockchain, digital finance, and inclusion : Cryptocurrency, FinTech, InsurTech, Regulation, ChinaTech, mobile security, and distributed ledger /: Cryptocurrency, FinTech, InsurTech, Regulation, ChinaTech, mobile security, and distributed ledger. (2017) - Lee, David (David Kuo Chuen); Deng, Robert H
No abstract available